2022
DOI: 10.1007/s11577-022-00844-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing or Widening the Gap? How the Educational Aspirations and Expectations of Turkish and Majority Families Develop During Lower Secondary Education in Germany

Abstract: Differences in educational goals between immigrants and the majority population have often been analysed at specific stages in their educational career. Little is known about longitudinal trajectories and the development of group differences over time. By applying common explanations (immigrant optimism, relative status maintenance, blocked opportunities, ethnic networks and information deficits), we derived specific hypotheses about the development of educational aspirations and expectations over time, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, the apparently low contribution of aspirations to the explanation of the ethnic choice effect in the TREE sample cannot be attributed to the fact that aspirations in this sample were measured only a few weeks before the end of compulsory schooling. Although it is theoretically plausible to assume that experiences in the form of missed entrance exams lead to a cooling-out of career goals and aspirations (Clark, 1960 ; Heckhausen and Tomasik, 2002 ; Neumeyer et al, 2022 ), i.e., an adjustment of the desired occupational career and the potentially still realizable training options leading to this goal. Accordingly, the mediating effect of aspirations may be underestimated when aspirations are measured close to the actual transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the apparently low contribution of aspirations to the explanation of the ethnic choice effect in the TREE sample cannot be attributed to the fact that aspirations in this sample were measured only a few weeks before the end of compulsory schooling. Although it is theoretically plausible to assume that experiences in the form of missed entrance exams lead to a cooling-out of career goals and aspirations (Clark, 1960 ; Heckhausen and Tomasik, 2002 ; Neumeyer et al, 2022 ), i.e., an adjustment of the desired occupational career and the potentially still realizable training options leading to this goal. Accordingly, the mediating effect of aspirations may be underestimated when aspirations are measured close to the actual transition.…”
Section: Resultsmentioning
confidence: 99%
“…The ethnic choice effect is partly due to the high educational and occupational aspirations of young people with a migration background. High aspirations among migrant youth are often explained by three theoretical arguments, which are not mutually exclusive: immigrant optimism; anticipated discrimination; and information deficit (Heath et al, 2008 ; Relikowski et al, 2012 ; Tjaden and Hunkler, 2017 ; Neumeyer et al, 2022 ). First , familiarity with and knowledge of the education system and educational alternatives tend to be poorer in families with a migration background (Kristen and Olczyk, 2013 ; Forster and van de Werfhorst, 2020 ).…”
Section: Gendered Ethnic Choice Effects— Theoretical Backgroundmentioning
confidence: 99%
“…Throughout literature, there are several arguments that specifically relate to the aspiration formation of immigrants, which have also been applied to the Turkish group (Neumeyer et al, 2022). For Turkish children particularly, prior research demonstrated the relevance of so-called immigrant optimism when forming realistic aspirations (e.g., Salikutluk, 2016).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…However, considering their lower levels of social origin and academic performance, immigrants lean more toward ambitious educational tracks. Researchers have found support for this phenomenon in early and middle educational stages in many Western countries ( Fekjær and Birkelund, 2007 ; Kristen et al, 2008 ; Kristen and Dollmann, 2010 ; Jackson et al, 2012 ; Tjaden and Scharenberg, 2017 ; Dollmann, 2021 ; Busse and Scharenberg, 2022 ; Neumeyer et al, 2022 ). In the following, we refer to the phenomenon of immigrants making more ambitious educational choices compared to natives of equal social origin and academic performance as the immigration-specific difference in educational choice .…”
Section: Introductionmentioning
confidence: 97%